2022
DOI: 10.3389/fimmu.2022.907125
|View full text |Cite
|
Sign up to set email alerts
|

Specific Antibody and the T-Cell Response Elicited by BNT162b2 Boosting After Two ChAdOx1 nCoV-19 in Common Variable Immunodeficiency

Abstract: Common variable immunodeficiency (CVID) patients have markedly decreased immune response to vaccinations. In this study we evaluated humoral and T cell-mediated responses against severe acute respiratory syndrome coronavirus-2 (SARS-Cov-2) with additional flow cytometric changes in CVID patients receiving booster vaccination with BNT162b2 after two ChAdOx1 nCoV-19. The BNT162b2 vaccine raised the anti-spike protein S immunoglobulin G over the cut-off value from 70% to 83% in CVID, anti-neutralizing antibody ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Previous data suggested a correlation between reduced specific humoral immune response and impaired specific T cellular immunity in CVID patients [ 17 , 27 ]. Our findings contrast this observation, with all CVID seroresponder and 5/6 non-seroresponder showing a robust polyfunctional CD4 + T cell immune response thus complementing previous reports of robust specific SARS-CoV-2 T cell responses in CVID patients with mild [ 28 ] and severe SARS-CoV-2 infections [ 29 ] as well as to COVID-19 vaccination [ 8 10 ] and other vaccines, such as influenza [ 30 , 31 ]. A limitation of our study is the relatively long period of collecting samples in CVID patients and HC.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Previous data suggested a correlation between reduced specific humoral immune response and impaired specific T cellular immunity in CVID patients [ 17 , 27 ]. Our findings contrast this observation, with all CVID seroresponder and 5/6 non-seroresponder showing a robust polyfunctional CD4 + T cell immune response thus complementing previous reports of robust specific SARS-CoV-2 T cell responses in CVID patients with mild [ 28 ] and severe SARS-CoV-2 infections [ 29 ] as well as to COVID-19 vaccination [ 8 10 ] and other vaccines, such as influenza [ 30 , 31 ]. A limitation of our study is the relatively long period of collecting samples in CVID patients and HC.…”
Section: Discussionsupporting
confidence: 87%
“…Findings on humoral immune response after COVID-19 vaccination are variable with frequencies of seroresponding CVID patients ranging from 20 to 95% [ 6 12 ]. A positive T cellular immune response was reported in 46–83% of CVID patients [ 8 , 10 15 ]. Reasons for the observed variability might include differences in methodology and different vaccination regimens as well as clinical, immunological, and genetic heterogeneity of CVID patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also highlighted by a recent Hungarian study, testing specific antibody and the T cell response elicited by BNT162b2 boosting after two ChAdOx1 shots in a cohort of CVID patients, compared with healthy control subjects. The authors also reported the AE profile, showing that CVID patients who had a worse immune response to vaccinations might have a slightly reduced rate of systemic side effects [31].…”
Section: Discussionmentioning
confidence: 99%
“…Additional longitudinal studies of vaccine efficacy in IEI are currently underway (NCT04852276) and it is hoped to provide further guidance to clinicians and patients regarding best methods to prevent COVID-19 in this population. 42,45,48,51,52,57,59,73…”
Section: Limitations and Future Needsmentioning
confidence: 99%